PSIKOANALISIS LACAN DALAM CERPEN MENYAMAK BABI: IDENTITAS, HASRAT, DAN KEKURANGAN - Kasimbara, Devi Cintia (UNIVERSITAS PGRI YOGYAKARTA, 2024)
ABSTRACT Irwan Abu Bakar's short story Menyamak Babi features an in-depth exploration of human nature through symbolism and metaphor. Using Lacan's psychoanalytic approach, this study examines the psychological and social dynamics depicted in the short story, particularly through the concepts of lack, desire, metaphor and metonymy. The short story tells the transformation of Or and Ang into pigs, which symbolically depicts greed, avarice, and moral conflict. This transformation not only represents personal conflict, but also provides social criticism of immoral behavior in society. In analysis, savagery symbolizes the dark side of humans, both as individuals and members of society. Or eventually overcomes his savagery and chooses the moral path as a writer, while Ang drowns in his greed, losing his humanity. The pig symbol is also used metonymically to criticize corrupt and greedy behavior in social and political life. The results of this study show that literary works can be a reflection of the complexity of human identity and social criticism, where symbolism and metaphor serve as a medium to understand human desires, shortcomings, and struggles in shaping their identity. Keywords: psychoanalysis, Lacan, lack, desire, metaphor, metonymy